Medicamentos à Base de Plantas: Contributo para o Aproveitamento dos Recursos Naturais Nacionais - João Cristóvão Martins (Formifarma, LDA., 2013)
In the last decade the European Union has harmonized the use of plants with medicinal and therapeutic purposes, based on different ethnopharmacological traditions. Currently, a considerable amount of monographs demonstrating the efficacy of several plants are already approved at community level, with indications for use either as well established authorization or traditional use registration. Several of these plants grow spontaneously in Portugal, indicating that it is possible their culture and exploitation by companies interested in their use, trade and export, as medicines. In this article the approved indications at Community level for plants that arise spontaneously in Portugal are presented, being also suggested the creation of a platform that brings together authorities, universities and economic actors to promote and facilitate the exploitation of these valuable national natural resources.